Remarks by Lt. Col. Sean Watts. (2017) - Watts, Sean
Abstract : We are still in the early days of the relationship between cyberspace and international law. In many respects, it is a relationship off to an unsteady and uncertain start. But a slow and sporadic trickle of governmental efforts to express or even to shape that relationship has emerged. To date, the most significant multinational clarification from states has been the deceptively modest concession that international law applies fully to cyberspace. States have at least made clear that the novelty and seemingly virtual nature do not exempt cyberspace from existing in international law.